Evaluation of Knowledge Management System Requirements According to ISO 30401 - Ali Kattafa, Wafaa; Raheem Younis Alazzawi , Firas (Journal of Economics and Administrative Sciences, 2025)
This Paper assesses the knowledge management system (KMS) requirements at Al-Ameed University concerning ISO 30401:2022. Specifically, the research aims to ascertain the degree to which international standards have been complied with and gaps that have been identified. A case study was conducted using field observations, interviews, and checklists to assess the institution’s compliance with the KMS framework. The level of implementation and documentation of knowledge management processes was assessed using a seven-point scale. The findings reveal that Al-Ameed University has severe gaps in knowledge creation, sharing, and support for knowledge management in terms of strategic leadership. While certain elements like availability of resources show high degrees of compliance, others like stakeholders need assessment and continuous improvement show weaknesses. The overall degree of compliance with the ISO 30401:2022 is 58.08%, having a gap of 41.92% to be bridged. This study shows there is an urgent need to improve knowledge-sharing systems, strengthen leadership engagement, and strategically align knowledge management with the university’s mission and goals. Their findings could help those academic institutions that want to improve knowledge governance and align themselves with internationally accepted standards shaking hands to become the key players in innovation and operational efficiencies. Future research should investigate KMS gap closure methodologies in other advanced situations/dimensions in higher educational settings.